Respons imun humoral pada pulpitis (Humoral immune response on pulpitis) - Trijoedani Widodo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Pulpitis is an inflammation process on dental pulp tissue, and usually as the continuous of caries. The microorganism in the caries is a potential immunogenic triggering the immune respons, both humoral and celluler immune responses. The aim of this research is to explain the humoral immune response changes in the dental pulp tissues of pulpitis. This research was done on three group samples: Irreversible pulpitis, Reversible pulpitis and sound teeth as the control group. The result showed that there were three pulpitis immunopathologic patterns: the sound teeth immunopathologic pattern showing a low humoral immune response, in a low level of IgG, IgA and IgM, the reversible pulpitis pattern showing that in a higher humoral immune response, IgG and IgA decreased but IgM increased, the irreversible pulpitis pattern showing that IgG and IgM increased, but it couldn't be repaired although it has highly immunity, and it showed an unusually low level of IgA. This low level of IgA meant that irreversible pulpitis had a low mucosal immunity.